Odpowiedzi

2010-03-16T21:24:06+01:00
A) 12y - (y + 5) = 10y - 1
12y -y -5 = 10y - 1
12y - y - 10y = -1 + 5
y = 4

b) 2(u - 5) + 15 = 3(u - 4) + 10
2u - 10 + 15 = 3u - 12 + 10
2u + 5 = 3u - 2
2u - 3u = -2 - 5
-u = -7
u = 7
2 2 2
Najlepsza Odpowiedź!
2010-03-16T21:24:10+01:00
A) 12y - (y + 5 ) = 10y-1
12y-y-5=10y-1
11y-10y=-1+5
y=4
B) 2 (u - 5) + 15 = 3 (u - 4) + 10
2u-10+15=3u-12+10
2u-3u=-12+10+10-15
-u=-7 |:(-1)
u=7
3 2 3
2010-03-16T21:29:23+01:00
A)
12y-(y+5)= 10y-1
12y-y-5= 10y-1
12y-y-10y= -1+5
12y-11y= 4
1y=4
B)
2(u-5)+15=3(u-4)+10
2u-10+15= 3u-12+10
2u-3u= -12+10-15+10
-1u= 7/(-1)
u= -7
1 1 1